Sistem Pakar Berbasis Android untuk Diagnosis Diabetes Melitus dengan Metode Forward Chaining - DEVI ASTRI NAWANGNUGRAENI (Computer Engineering Departement, Universitas Komputer Indonesia, 2021)
Diabetes Mellitus is the biggest cause of death disease. This is beause the lack of public knowledge about the symptoms of disease which is caused delayed in handling. This article presents the development of an expert system application used as a Diabetes Mellitus diagnosis tool on Android mobile. The purpose of application is to detect Diabetes Mellitus based on the type of Diabetes Mellitus symptoms and determine the possibility of the disease occurred. The method for developing an expert system is forward chaining. The implementation of forward chaining method is used to gather information then proceed by applying reasoning with the if-then rule as a result of the conclusion of a diagnosis according to symptoms. The stages in developing this expert system application use the Expert System Development Life Cycle (ESDLC). The result of its development is an expert system used for diagnosis of Diabetes Mellitus according to the symptoms experienced. The expert system application is implemented on the Android mobile. This expert system application displays specific results to displaying a diagnosis of Diabetes Mellitus and displays the percentage of the possibility of the disease. Keywords – Android; Diabetes Mellitus; Diagnose; Forward chaining; Expert system.